2022
DOI: 10.3389/fphar.2022.969257
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visual analysis of blood-testis barrier research

Abstract: Background: Extensive research on the blood-testis barrier has been undertaken in recent years. However, no systematic bibliometric study has been conducted on this subject. Our research aimed to identify the hotspots and frontiers of blood-testis barrier research and to serve as a guide for future scientific research and decision-making in the field.Methods: Studies on the blood-testis barrier were found in the Web of Science Core Collection. VOSviewer, CiteSpace, and Microsoft Excel were used to conduct the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 114 publications
1
2
0
1
Order By: Relevance
“…According to another study by Cheau-Feng Lin et al, it was shown that traumatic rib fractures were associated with mortality and had similar results with our study (10).…”
Section: Discussionsupporting
confidence: 91%
“…According to another study by Cheau-Feng Lin et al, it was shown that traumatic rib fractures were associated with mortality and had similar results with our study (10).…”
Section: Discussionsupporting
confidence: 91%
“…The aggravation of oxidative stress is also detrimental to the maintenance of BTB integrity. 49,53 Excessive oxidative stress in testicular tissue can cause BTB damage in obese male mice, as well as BTB damage in mice exposed to polystyrene microplastics. 54,55 In this study, PS-NP poisoning led to the aggravation of oxidative stress in obese mice, so it is speculated that the aggravation of BTB damage is also due to the exposure of PS-NPs in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, exposure to PS‐NPs led to a decrease in testosterone secretion in obese mice, which may indirectly lead to the disruption of BTB integrity. The aggravation of oxidative stress is also detrimental to the maintenance of BTB integrity 49,53 . Excessive oxidative stress in testicular tissue can cause BTB damage in obese male mice, as well as BTB damage in mice exposed to polystyrene microplastics 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometri; yayınlanan bilimsel makale, kitap ve diğer yayınların sayısal analizler ve istatistikler yardımıyla disiplinlerin ilerlemesini değerlendirmek ve izlemek için bir yöntem olarak tanımlanır (9). Bibliometrik analiz ise; belirli bir alanda belirli bir dönemde ve belirli bir bölgede kişiler ya da kurumlar tarafından üretilmiş yayınların ve bu yayınlar arasındaki ilişkilerin kalitatif ve kantitatif analizidir (10,11).…”
unclassified